The Role of Abdominal Computed Tomography in Determining Perforation Findings and Site in Patients with Gastrointestinal Tract Perforation - Ilgar, M.; Elmali, M.; Nural, M.S. (Turkish Association of Trauma and Emergency Surgery, 2013)
BACKGROUND: In this study, we investigated the role of abdominal computed tomography (CT) in determining perforation findings and site in patients with gastrointestinal tract perforation. METHODS: Preoperative abdominal CT scans of 47 patients who had surgically proven gastrointestinal tract perforation between July 2007 and July 2010 were reviewed retrospectively. The presence of free air, leakage of contrast material, wall thickness, wall discontinuity, abscess, free fluid, and phlegmon were investigated for each patient. The site of perforation was estimated in light of these findings and compared with the surgical outcomes. RESULTS: Perforation sites were determined correctly in 85.7% of patients with gastroduodenal perforation, 85.7% of patients with small bowel perforation, 69.2% of patients with large bowel perforation, 100% of patients with rectum perforation, 90.9% of patients with appendix perforation, and 82.9% of all patients according to the abdominal CT findings. The most common CT finding in gastrointestinal tract perforation was free fluid, with a rate of 89.4%. The rates of other findings were as follows: free air 76.6%, segmental wall thickening 48.9%, wall discontinuity 25.5%, abscess 12.8%, and phlegmon 10.6%. Of 30 patients who received oral contrast, 7 (23.3%) had extraluminal contrast leakage. CONCLUSION: CT is very effective in determining gastrointestinal tract perforation findings and the site of perforation.
Gastrointestinal Kanal Perforasyonlarında Perforasyon Bulgularının Ve Yerinin Saptanmasında Karın Bilgisayarlı Tomografisinin Rolü
Keywords: Computed Tomography; Intestinal Perforation; Spiral Computed Tomography